GENESIS OF THE FORMATION OF THE BASIC VALUES OF UKRAINIAN SOCIETY DURING THE XVI – XVII CENTURIES - Larin S.V. (Pressing Problems of Public Administration, 2017)
The article deals with problems of formation of basic values as a factor of consolidation of Ukrainiansociety in the historical aspect, which is one of the most controversial issues among scholars,politicians and experts of Ukraine and abroad. The study of the genesis of the formation of the basicvalues of Ukrainian society in the period of XVI-XVII centuries, in the opinion of the author of thearticle, will contribute to the study of theoretical and methodological foundations of the problem ofprotection of national values as a priority area of state administration in the  eld of national security.